2019
DOI: 10.2217/epi-2019-0093
|View full text |Cite
|
Sign up to set email alerts
|

CircPLK1 sponges miR-296-5p to facilitate triple-negative breast cancer progression

Abstract: Aim: To investigate the role of circRNAs in triple-negative breast cancer (TNBC) and the underlying mechanisms. Materials & methods: We performed circRNA microarrays to explore the expression profiles of TNBC cell lines. Experiments in vitro and in vivo were conducted to explore the effects of circPLK1 on tumor proliferation and metastasis as well as the interaction between circPLK1, miR-296-5p and PLK1 in TNBC. Results & conclusion: CircPLK1 was significantly upregulated in TNBC and associated with po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 39 publications
1
35
0
Order By: Relevance
“…Circular RNAs have been reported to affect the function of their genes of origin via sponging of miRNAs. 21,27,28 We showed that circ_0060745 was derived from exon 9 to exon 10 of linear CSE1L and that circ_0060745 sequestered miR-4736. Therefore, we evaluated whether CSE1L was a downstream target gene of the circ_0060745/miR-4736 axis.…”
Section: Microrna 4736 Suppressed Proliferation and Metastasis Via Tamentioning
confidence: 91%
“…Circular RNAs have been reported to affect the function of their genes of origin via sponging of miRNAs. 21,27,28 We showed that circ_0060745 was derived from exon 9 to exon 10 of linear CSE1L and that circ_0060745 sequestered miR-4736. Therefore, we evaluated whether CSE1L was a downstream target gene of the circ_0060745/miR-4736 axis.…”
Section: Microrna 4736 Suppressed Proliferation and Metastasis Via Tamentioning
confidence: 91%
“…It was also revealed that circUBAP2 was correlated with tumour size, advanced TNM stage and worse prognosis in TNBC and promoted tumour progression by sponging miR‐661 to upregulate MTA1 136 . Furthermore, circAGFG1, circKIF4A, circPLK1 and circRAD18 were revealed to promote malignant progression of TNBC by sponging corresponding tumour suppressive miRNAs as well 137‐140 . In addition, Zhang et al 141 found that circRNA_069718 can promote the proliferation and invasion of cancer cells by activating the Wnt/β‐catenin pathway, thereby promoting the malignant progression of TNBC.…”
Section: Circular Rnasmentioning
confidence: 98%
“…The higher expression levels of circKIF4A correlated with poor OS in TNBC patients (Tang et al, 2019). CircPLK1 was also upregulated in TNBC tissues and correlated with larger tumor size, lymph node positivity, advanced TNM stage and poor OS (Kong Y. et al, 2019). It promotes TNBC metastasis by sponging miR-296-5p and regulating PLK1 expression (Kong Y. et al, 2019).…”
Section: Breast Cancer (Bc)mentioning
confidence: 99%